RHETORICAL MOVES IN INTRODUCTIONS: PROMPT-BASED WRITING TRIAL RESULTS - Ganie, Rohani; Sinar, Tengku Silvana; Syahputra, Fikry Prastya; Veronica, Afryna (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2025)
This study investigates the role of writing prompts to create appropriate introduction section in research article. The study analyzes three texts generated from ChatGPT by using three distinct prompts formulated based on the writing prompt model proposed by Kroll Reid, and Chapman. Using a qualitative descriptive approach, the resulting texts were analyzed at the macro level to determine the realization of rhetorical moves. The findings indicate that prompt design significantly affects the quality and rhetorical completeness of the Introductions. Prompt 3, which contained more explicit instructions regarding gap identification and research significance, produced a text most closely aligned with all three moves of the CARS model. In contrast, the more general prompts led to partial or less structured realizations of the rhetorical elements. These results suggest that structured and genre-sensitive prompts can effectively guide writers when they seek Artificial Intelligence (like ChatGPT) assistance in writing research article. This study also highlights the pedagogical potential of prompt-based writing as a strategy to support academic writing instruction in higher education especially with the combination of newest technology.